KEKERASAN PERMUKAAN RESIN-MODIFIED GLASS IONOMER CEMENT SETELAH PERENDAMAN DALAM AIR SUNGAI (Penelitian Menggunakan Air Sungai Desa Anjir Pasar, Barito Kuala, Kalimantan Selatan) - Shella, Selvia; Ichrom Nahzi, Muhammad Yanuar; Erlita, Isyana (FKG Unlam, 2017)
ABSTRACTBackground: Resin-modified glass ionomer cement is a hybrid form of glass ionomer cement and resin. Added resin (HEMA) in this material allows its characteristics to improve, especially its resistance of acid. The water of Desa Anjir Pasar River has acidic nature with pH as low as 3-5. Purpose: The aim of this study is to find surface hardness difference of resin modified glass ionomer cement after it was soaked in the water of Anjir Pasar Village River compared to aquadest-soaked materials. Method: The study used resin-modified-glass ionomer cement specimens prepared in cylindrical-shaped with diameter of 10 mm and thickness of 2 mm. One group was soaked in aquadest (control) and another group in river water with pH of 3 for 4.5 days (equivalent to 3 years of exposure) before measuring the surface hardness of each group. Data was analyzed using parametric analysis Independent T-Test 95% (Î± = 0.05) which presented p value = 0.003 (p<0.05). Result: The result indicated that there was a significant difference of surface hardness between resin modified glass ionomer cement soaked in the water of Anjir Pasar Village River with pH of 3 for 4.5 days and in the aquadest. Conclusion: Based in this study there is a great differences of hardness on resin-modified glass ionomer cement materials that are immersed in river water to sterilize aquades.Keywords: Resin-Modified Glass Ionomer Cement, river water, surface hardness